TREND COFFEE SHOP DI DEPOK DAN STRATEGI DALAM BERTAHAN DI TENGAH BANYAKNYA COFFEE SHOP DI DEPOK - Arbi Haryanto; Irfan Maulana; Muhamad Latief; Muhammad Akbar Nuansaandjie (CV. Multi Kreasi Media, 2023)
In Indonesia the amount of coffee consumption is increasing, especially among teenagers. Many teenagers, especially in Depok, drink coffee almost every day at their favorite coffee shop. Unfortunatly these habits lead to a consumptive lifestyle. The purpose of this research is to describe the coffee shop trend among teenagers in Depok. The theory used in this study is the phenomenological theory. The methodology used in this study is a qualitative methodology with a phenomenological perspective. The results of this study indicate that the existence of coffee shops is popular with young consumers, due to the convenience of the place, the concept provided by the coffee shop owner, and affordable prices.